Semantic and hermeneutic analysis of the terms chaka, chakana and chakata - Cisneros Ayala, Claudia (2021)
This paper studies the resemantization and meaning determination of the Quechua terms chaka, chakana and chakata. The research focuses on the explanation of the morphological structure. In the procedure we start from the work of the Lexicon of 1560 where we find the term chakata with the meaning of cross. The philological-hermeneutic method and the use of Quechua dictionaries were chosen for the work. As a result of the analysis, the term chakata has chaka as lexeme, which indicates the base element that makes «X» elements cross. Chakana would be the object with which the entities are crossed. Finally, the word chakata, agglutinates the suffix -ta with meaning ‘inter’ or ‘between’, being the word as a whole chakatay ‘to cross’. In conclusion, chakata would mean ‘inter-cross-’; in a philosophical sense, it forms the basis that intertwines, «X» elements within nature and human actions.